Play-mirth theory: a cognitive appraisal theory of humor - Hatzithomas, Leonidas (Frontiers in Psychology, 2024)
This work aims to introduce a general theory of humor elicitation and appreciation, the play-mirth theory, which is based on the cognitive appraisal perspective. Two experiments test the theory's central hypothesis: that is, to experience humor, one must interpret (a) a stimulus as a playful turn and (b) the turn as consistent with their motives. In the first experiment, 104 undergraduate students rated the appraisal determinants of successful and failed humor experiences that they recalled. In the second experiment, appraisals of playful turn (i.e., present, or absent), situational state (i.e., motive-inconsistent/motive-consistent), and motivational state (punishment/reward) were manipulated. Overall, 150 undergraduate students were exposed to the manipulated stimuli and answered a structured questionnaire. The findings provide the first experimental evidence that two appraisals (i.e., playful turn and motive-consistency) do elicit humor. Play-mirth hypothesis sufficiently differentiates humorous from nonhumorous experiences as well as mirth from other positive emotions such as joy, and relief.